Occurrence of Psoriatic Arthritis during Interferon Beta 1a Treatment for Multiple Sclerosis. (15th April 2014) - Toussirot, Éric; Béreau, Matthieu; Bossert, Marie; Malkoun, Imad; Lohse, Anne
Abstract : Interferon beta (IFN- β ) is the first line therapy of relapsing-remitting multiple sclerosis. IFN- β is a cytokine that can contribute to the development of systemic autoimmune disease including psoriasis. The development or the exacerbation of psoriasis during IFN- β treatment has been previously observed. We report the occurrence of arthritis and dactylitis in a multiple sclerosis patient with preexisting psoriasis diagnosed as a psoriatic arthritis. The IL-23/Th17 pathway is involved in psoriasis and psoriatic arthritis and it has been suggested that IFN- β therapy in patients with Th17-mediated disease may be detrimental. Together with previous similar reports, our case suggests that IFN- β should certainly be used with caution in patients with concomitant systemic autoimmune disease with IL-23/Th17 involvement.